Penentuan Waktu Optimal Pembuatan Dished End Dengan Metode Waktu Standard Pada Sterilizer Door Diameter 2100 mm - Dedi Panuju; Haniza Haniza (Universitas Medan Area, 2018)
In execution of activity of factories required by labour taking charge of to execution of the duties and have membership in the field of its are each. Calculation and usage of careful time will support employment scheduling which have been made for every work process. Data which collected at this researchs are time which required to do an activities identities at each activity units. Data which tested obtained uniformity of the data with level of convident limit of 95/5%, so that determinable summed up the required observations. After obtained by is cycle time then countable the normal time, by reckoning rating factor (adjustment according to Westinghouse) that is skill factor, effort, consistency and working condition. Based on normal time which then added with diffuseness and adjustment factor which wanted for each element From result calculation at each working activity unit in making of Dished, End, hence obtained by is standard time as follows : unit standard time Forklift I, unit standard time Marking, unit standard time Inspection I, unit standard time Cutting, standard time Crane I, unit standard time Dishing, unit standard time Inspection II, unit standard time Crane II, unit standard time Flanging, unit standard time Forklift II, unit standard time Sand Blasting, unit standard time Crane III, and unit standard time Turning was. Causing total standard time for finish making an unit Dished End at Sterilizer Door diameter of 2100 mm is 2231,69 minute. working, hence obtained by is standard time.